Emerging therapeutic strategies for cystinosis - Goodyer, Paul; Torban, Elena (Frontiers in Pediatrics, 2025)
For over 40 years, oral cysteamine has been the mainstay of therapy for cystinosis. While it has been of great benefit, slowing organ deterioration and prolonging life, cysteamine is not well tolerated and may not rescue all pathogenic mechanisms driving the disease. Of late, research groups around the world have been pursuing various novel therapeutic strategies. Here we select just four of many examples - two that address events downstream of the missing Cystinosin protein and two that aim to address the upstream CTNS mutation. Our aim is to update the cystinosis community on some of the exciting work in progress. We have drawn from preliminary reports and oral presentations at cystinosis meetings. While each approach requires further work and critical analysis, the sheer number and variety of these potential therapies is cause for hope.